The role of tobacco advertising and promotion: themes employed in litigation by tobacco industry witnesses - Goldberg, Marvin E (BMJ Group, 2006)
OBJECTIVES: To identify key themes related to tobacco advertising and promotion in testimony provided by tobacco industry‐affiliated witnesses in tobacco litigation, and to present countervailing evidence and arguments. METHODS: Themes in industry testimony were identified by review of transcripts of testimony in the Tobacco Deposition and Trial Testimony Archive (http://tobaccodocuments.org/datta) from a sample of defence witnesses, including three academic expert witnesses, six senior executives of tobacco companies, and one industry advertising consultant. Counterarguments to the themes embodied in defence testimony were based on information from peer‐reviewed literature, advertising trade publications, government reports, tobacco industry documents, and testimony provided by expert witnesses testifying for plaintiffs. RESULTS: Five major themes employed by defence witnesses were identified: (1) tobacco advertising has a relatively weak “share of voice” in the marketing environment and is a weak force in affecting smoking behaviour; (2) tobacco advertising and promotion do not create new smokers, expand markets, or increase total tobacco consumption; (3) the tobacco industry does not target, study, or track youth smoking; (4) tobacco advertising and promotion do not cause smoking initiation by youth; and (5) tobacco companies and the industry adhere closely to relevant laws, regulations, and industry voluntary codes. Substantial evidence exists in rebuttal to these arguments. CONCLUSIONS: Tobacco industry‐affiliated witnesses have marshalled many arguments to deny the adverse effects of tobacco marketing activities and to portray tobacco companies as responsible corporate citizens. Effective rebuttals to these arguments exist, and plaintiffs' attorneys have, with varying degrees of success, presented them to judges and juries.